Sectoral analysis of the effectiveness of bank risk capital in the Visegrad Group countries - Nocoń, Aleksandra; Pyka, Irena (Journal of Business Economics and Management, 2019)
Bank risk capital (capital at risk) is identified with the value of banks’ own funds maintaining to absorb potential losses and protect against insolvency. It is calculated for the capital adequacy ratios, recommended by the Basel Committee on Banking Supervision. On other words, it is a kind of banks’ capital that financing securing the negative effects of risk occurring. A comparative analysis of effectiveness of bank risk capital in the Visegrad Group countries, constituting the main objective of the study, results from the needs indicated in the already conducted preliminary research. In the article, statistical and econometric methods were used, based on linear regression models. The conducted research were aimed to verify the research hypothesis stating that in the analyzed banking sectors of the Visegrad Group countries there is a positive correlation between banks' profitability and a level of their bank risk capital. The study indicated that net profit of the analyzed banking sectors increases with a growth of total own funds, while profitability is diversified in individual countries. Declining operational efficiency results from the growing cost of obtaining and maintaining risk capital.